Microstructure analysis and nonlinear/linear optical parameters of polymeric composite films based PVAL for wide optical applications. (22nd July 2021) - Ali, H Elhosiny; Abdel-Aziz, M M; Khairy, Yasmin; Zahran, H Y; Algarni, H; Yahia, I S; El-Shamy, E F; Sayed, M A; Maged, Fatma Abdel; Sanaa, M F
Abstract: New proposed optical polymeric systems of PVAL/Cu particles have been synthesized by casting proceed to stand their NL (Nonlinear)/L (Linear) optical properties for various optical applications. Herein, the structure of the composites with various wt% of Cu was analyzed by the diffraction of X-ray (XRD) and FTIR. The semi-crystalline nature of PVAL has been influenced by Cu concentration as presented in XRD and Gaussian fitting. FTIR results confirm the strong interaction between Cu and polymer via the main hydroxyl group of the matrix. The morphological surfaces of pristine and doped PVAL have been measured. Optical measurement shows a redshift of the absorption edge. Moreover, the indirect transition bandgap decreased gradually with the Cu-level. This reflects the presence of localized states in the prohibited band facilities the electrons transition from HOMO to LUMO. The extinction coefficient and Urbach energy of the films have been enhanced. The ε o (static) and ε ∞ (high-frequency) dielectric variables are calculated. NL/L refractive index and susceptibility are estimated from the bandgap values. The optical limiting of the composite films has been tested using a green diode laser and He-Ne laser. The PVAL sample with high Cu wt% is an optical system capable of different technical applications, such as solar cells, optoelectronic devices, electronic apparatus, and optical filters.